Unemployment in the regional context in Latvia - Hohlova, Vera (Business: Theory and Practice, 2024)
This paper sets out a methodological framework for identifying and mitigating unemployment problems in different regions. The study is based on the 2020 and 2023 Latvian Unemployment Surveys. The study includes a comprehensive review of the relevant scientific literature, policy and regulatory frameworks, the development of a multilevel research methodology and tools, an analysis of the research results, in-depth discussions of the identified problems in the context of existing scientific knowledge, and a set of key conclusions and proposed measures to address these problems. By structuring the paper in this way, it offers a holistic and systematic approach to understanding and addressing regional unemployment problems. The study contributes to the ongoing dialogue on regional economic disparities and highlights opportunities for more inclusive, sustainable and equitable labour markets.